Identification of a gene network driving the attenuated response to lipopolysaccharide of monocytes from hypertensive coronary artery disease patients - Lu, Chang; Donners, Marjo M. P. C.; de Baaij, Julius B. J.; Jin, Han; Otten, Jeroen J. T.; Manca, Marco; van Zonneveld, Anton Jan; Jukema, J. Wouter; Kraaijeveld, Adriaan; Kuiper, Johan; Pasterkamp, Gerard; Mees, Barend; et al. (Frontiers in Immunology, 2024)
The impact of cardiovascular disease (CVD) risk factors, encompassing various biological determinants and unhealthy lifestyles, on the functional dynamics of circulating monocytes-a pivotal cell type in CVD pathophysiology remains elusive. To elucidate the influence of CVD risk factors on monocyte transcriptional responses to an infectious stimulus, we conducted a comparative analysis of monocyte gene expression profiles from the CTMM -CIRCULATING CELLS Cohort of coronary artery disease (CAD) patients, both pre-and post-lipopolysaccharide (LPS) stimulation. Notably, our investigation revealed a highly significant negative correlation between blood pressure levels and monocyte responsiveness to LPS (ρ< -0.4; P<10 -80 ). Leveraging gene co-expression and regulatory networks, we identified a gene module closely linked to diastolic blood pressure and delineated the pivotal transcription factors controlling the hub genes within this module. Our findings suggest that monocyte responses to infectious stimuli, such as LPS, may be attenuated in CAD patients with elevated diastolic blood pressure. This attenuation appears associated with a diminished LPS-induced suppression of oxidative phosphorylation. Subsequently, we employed this identified gene module to screen potential drugs capable to reverse the attenuated LPS response, utilizing the LINCS L1000 database. We identified the serine-threonine inhibitor MW-STK33-97 as a drug candidate capable of reversing this effect. Whether the identified gene module is a mere indicator of, or causal factor in diastolic blood pressure and the associated dampened LPS responses remains to be determined.